Development and Validation of the Thought Impact Scale: A Measure of Subconscious Connectedness - Palsson, Olafur S. (The American journal of clinical hypnosis, 2020)
The Thought Impact Scale (TIS) is a new questionnaire designed to measure the theorized psychological characteristic of subconscious connectedness, defined as the degree to which nonconscious mental functions spontaneously interact with, and are accessible to, conscious awareness in everyday life. A principal reason for developing the TIS was the expectation that subconscious connectedness influences hypnosis treatment responses and seeking of hypnosis treatment. Two studies involving 1,216 subjects were carried out to validate the questionnaire. The TIS exhibited high internal consistency (Cronbach's alpha of 0.93 and 0.95), good one-month test-retest reliability (r = 0.89), and convergent validity evidenced by substantial correlations with other measures hypothesized to partly assess the same construct: Absorption (r = 0.70), fantasy proneness (r = 0.54), dissociation (r = 0.50), and emotional empathy (r = 0.39). TIS scores were approximately normally distributed, higher in females than males, and declining with age. Exploratory factor analysis showed the TIS to be composed of a single dominant factor. High TIS scorers were 2.5 times as likely as low scorers to have undergone hypnosis treatment, 2.6 times as likely to report at least moderate benefit after hypnosis treatment, and 3.8 times as likely to consider themselves highly hypnotizable. High TIS scorers also more frequently reported being highly creative, art lovers, intuition-reliant, absentminded, spontaneous, novelty-seeking, and prone to form intense relationships. The TIS is a reliable and valid measure that is likely to be useful in clinical hypnosis practice and hypnosis research and for quantifying communication between conscious and nonconscious mental functions.